2014
DOI: 10.1038/mt.2013.155
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Myoblast Transplantation for Oculopharyngeal Muscular Dystrophy: a Phase I/Iia Clinical Study

Abstract: Oculopharyngeal muscular dystrophy (OPMD) is a late-onset autosomal dominant genetic disease mainly characterized by ptosis and dysphagia. We conducted a phase I/IIa clinical study (ClinicalTrials.gov NCT00773227) using autologous myoblast transplantation following myotomy in adult OPMD patients. This study included 12 patients with clinical diagnosis of OPMD, indication for cricopharyngeal myotomy, and confirmed genetic diagnosis. The feasibility and safety end points of both autologous myoblast transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 27 publications
(33 reference statements)
1
81
0
2
Order By: Relevance
“…Over the last few years, several potential treatment approaches have emerged [16,18,[32][33][34][35][36][37][38], some of which are described in Table 1. Given that these treatment strategies are limited to reducing the symptoms of the disease, it is vital that new therapies are developed that directly target the underlying mutation in OPMD.…”
Section: Arc Publishingmentioning
confidence: 99%
“…Over the last few years, several potential treatment approaches have emerged [16,18,[32][33][34][35][36][37][38], some of which are described in Table 1. Given that these treatment strategies are limited to reducing the symptoms of the disease, it is vital that new therapies are developed that directly target the underlying mutation in OPMD.…”
Section: Arc Publishingmentioning
confidence: 99%
“…La conformation anatomique ainsi que le mouvement respiratoire compliquent l'étude du diaphragme, mais son rôle fonctionnel et son implication dans de nombreuses maladies justifient ces efforts (Mead et al 2014). Un autre exemple, parmi une multitude : la thérapie cellulaire de patients atteints de dystrophie musculaire oculo-pharyngée (Périé et al 2014). Une imagerie de haute résolution des muscles laryngés injectés avec des myoblastes homologues pourrait permettre de suivre, sinon directement les cellules thérapeuti-ques éventuellement marquées avec un agent de contraste, tout au moins leur impact éventuel sur la progression des lésions dégénératives.…”
Section: ) (Voirunclassified
“…However, it might be feasible to use myoblast therapy to treat muscular dystrophies with fewer, small affected muscles, such as oculopharyngeal muscular dystrophy (OPMD) and facioscapulohumeral muscular dystrophy. In support of this possibility, a phase I/IIa trial of patients with OPMD was conducted [31]. They reported improvement in the quality of life for all patients (n = 12), a cell dose-dependent improvement in swallowing, no subsequent decline in swallowing after initial myotomy and cell transplantation, and no adverse events [31].…”
Section: Muscular Dystrophy and The Rationale For Stem Cell Therapy Fmentioning
confidence: 99%
“…In support of this possibility, a phase I/IIa trial of patients with OPMD was conducted [31]. They reported improvement in the quality of life for all patients (n = 12), a cell dose-dependent improvement in swallowing, no subsequent decline in swallowing after initial myotomy and cell transplantation, and no adverse events [31]. Subsequent efforts have also focused on identifying other stem cell populations for regenerating dystrophic muscle, primarily myogenic stem cells that participate directly in muscle repair, although a recent study also demonstrated the importance of other cells such as regulatory T cells that indirectly influence this process in damaged muscle [32].…”
Section: Muscular Dystrophy and The Rationale For Stem Cell Therapy Fmentioning
confidence: 99%